Could payments for environmental services improve rangeland management in Central Asia, West Asia and North Africa? - Dutilly-Diane, Celine; McCarthy, Nancy; Turkelboom, Francis; Bruggeman, Adriana; Tiedemann, James; Street, Kenneth; Serra, Gianluca (International Food Policy Research Institute, 2007)
Although several institutional and management approaches that address the degradation of the rangelands have been tested in the dry areas of Central and West Asia and North Africa (CWANA), impact has been limited. Nonetheless, the development of National Action Plans to combat desertification highlights the interest of governments to tackle this issue. Payment for Environmental Services (PES) may be a viable policy option, though, to date, most PES programs have focused on the management of different resources (forests, watersheds). The purpose of this paper is to examine whether PES could be a viable option to promote sustainable rangelands management in the dry rangelands of CWANA. Specifically, it focuses on the scientific gaps and knowledge related to the local and global environmental services produced by rangelands and addresses questions related to the beneficiaries of these services. Institutional conditions necessary for the implementation of such schemes are discussed.